Thermal Performance of Three Sided Artificially Roughened Double Duct Parallel Flow Solar Air Heater - Kant, Chander; Kumar, Prashant; Gill, Ankur; Dhiman, Dhiraj Parkash (Asian Journal of Engineering and Applied Technology, 2018)
A solar air heater is basically a heat exchanger, which intercepts the incident solar radiation, converts it into heat and finally transfers this heat to a working fluid for an end use system. The mode of air flowing in the ducts of a solar air heater is one of the most significant aspects concerned with solar air heater which dominantly affect. A double duct parallel flow artificially roughened solar air heater with three sides of the absorber plate is investigated in the current study. Unlike the conventional model of solar air heater with only one sided roughened absorber plate, a novel solar air heater with three artificially roughened absorber plate is used so that the surface area of the absorber plate is increased which ultimately increases the rate of heat transfer. Additionally, a double duct parallel flow arrangement through inner and outer duct of solar air heater is considered order to enhance the heat transfer rate. A numerical investigation of the heat transfer and friction factor characteristics of a double duct parallel flow three sided artificially roughened solar air heater has been carried out. A commercial finite volume CFD code ANSYS FLUENT is used to simulate turbulent air flow through artificial roughened solar air heater. Governing equations of the fluid flow and heat transfer i.e. Navier-Stokes equation and energy equation are solved with RNG k-ε turbulence model. Nine different configuration of square rib are studied with relative roughness pitch (P/e = 5-10) and relative roughness height (e/D = 0.03-0.06). The Reynold number of the flow is varied from 2500 to 16000.